A Comparative Study of Functionalized High‐Purity Carbon Nanotubes towards the V(IV)/V(V) Redox Reaction Using Cyclic Voltammetry and Scanning Electrochemical Microscopy. Issue 4 (28th December 2016) - Steimecke, Matthias; Rümmler, Stefan; Schuhmacher, Nils‐Frederik; Lindenberg, Titus; Hartmann, Mark; Bron, Michael
Abstract: Functionalized high purity carbon nanotubes (CNTs) with various amounts of oxygen containing surface groups were investigated towards the relevant redox reactions of the all‐vanadium redox flow battery. The quinone/hydroquinone redox peaks between 0.0 and 0.7 V vs. Ag|AgCl|KClsat. were used to quantifying the degree of functionalization and correlated to XPS results. Cyclic voltammetry in vanadyl sulfate‐containing 3 M H2 SO4 as a common supporting electrolyte showed no influence of the amount of surface groups on the V(IV)/V(V) redox system. In contrast, the reactions occurring at the negative electrode (V(II)/V(III) and V(III)/V(IV)) are strongly affected by oxygen surface groups. However, under modified experimental conditions, SECM experiments detecting the consumption of VO 2+ molecules by CNT thin films in pH=2 solution show improved onset potentials with increased surface oxygen content up to ∼ 3 at%. Further increase in surface oxygen up to 8 at% led to minor improvement. These dissimilar results under different experimental conditions are rationalized by suggesting that oxygen functional groups do not form the active site for the V(IV)/V(V) reaction but wetting of the catalyst layer is of high importance. Abstract :